The effect of targeting Tie2 on hemorrhagic shock-induced renal perfusion disturbances in rats - van Leeuwen, Anoek L. I.; Dekker, Nicole A. M.; Van Slyke, Paul; de Groot, Esther; Vervloet, Marc G.; Roelofs, Joris J. T. H.; van Meurs, Matijs; van den Brom, Charissa E. (Intensive care medicine experimental, 2021)
Background Hemorrhagic shock is associated with acute kidney injury and increased mortality. Targeting the endothelial angiopoietin/Tie2 system, which regulates endothelial permeability, previously reduced hemorrhagic shock-induced vascular leakage. We hypothesized that as a consequence of vascular leakage, renal perfusion and function is impaired and that activating Tie2 restores renal perfusion and function. Methods Rats underwent 1 h of hemorrhagic shock and were treated with either vasculotide or PBS as control, followed by fluid resuscitation for 4 h. Microcirculatory perfusion was measured in the renal cortex and cremaster muscle using contrast echography and intravital microscopy, respectively. Changes in the angiopoietin/Tie2 system and renal injury markers were measured in plasma and on protein and mRNA level in renal tissue. Renal edema formation was determined by wet/dry weight ratios and renal structure by histological analysis. Results Hemorrhagic shock significantly decreased renal perfusion (240 ± 138 to 51 ± 40, p < 0.0001) and cremaster perfusion (12 ± 2 to 5 ± 2 perfused vessels, p < 0.0001) compared to baseline values. Fluid resuscitation partially restored both perfusion parameters, but both remained below baseline values (renal perfusion 120 ± 58, p = 0.08, cremaster perfusion 7 ± 2 perfused vessels, p < 0.0001 compared to baseline). Hemorrhagic shock increased circulating angiopoietin-1 ( p < 0.0001), angiopoietin-2 ( p < 0.0001) and soluble Tie2 ( p = 0.05), of which angiopoietin-2 elevation was associated with renal edema formation (r = 0.81, p < 0.0001). Hemorrhagic shock induced renal injury, as assessed by increased levels of plasma neutrophil gelatinase-associated lipocalin (NGAL: p < 0.05), kidney injury marker-1 (KIM-1; p < 0.01) and creatinine ( p < 0.05). Vasculotide did not improve renal perfusion ( p > 0.9 at all time points) or reduce renal injury (NGAL p = 0.26, KIM-1 p = 0.78, creatinine p > 0.9, renal edema p = 0.08), but temporarily improved cremaster perfusion at 3 h following start of fluid resuscitation compared to untreated rats (resuscitation + 3 h: 11 ± 3 vs 8 ± 3 perfused vessels, p < 0.05). Conclusion Hemorrhagic shock-induced renal impairment cannot be restored by standard fluid resuscitation, nor by activation of Tie2. Future treatment strategies should focus on reducing angiopoietin-2 levels or on activating Tie2 via an alternative strategy.